Menilik Manajemen Bimbingan Kelompok di SMKN 1 Cijulang - Elsa Istiqomah; Rosiva Febrian; Agung Jaelani (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to determine the implementation of group guidance management at SMK Negeri 1 Cijulang. The method used in this research is a qualitative approach with qualitative descriptive methods. Data collection techniques in this research use techniques adapted to the situation and conditions in the research field, including interview, observation and documentation techniques. The research results showed that the group guidance management program was not implemented because there were several inhibiting factors in its implementation, including guidance and counseling teachers having difficulty arranging assessment time, class hours not being given due to limited classroom space, and class hours being full because they were mostly used for practicums. This results in group guidance management not being implemented well.